Evolution and perspectives of Spanish in Russian school system - J. Torres Hernández (Ибероамериканские тетради)
The article examines from various points of view the  role of the  Spanish language  in   the    Russian    system   of    primary    and  secondary education,  both  public    and   private,  paying   special   attention to the  experience of  schools participating in the  Bilingual  Sections program of the  Spanish Ministry of Education and Training. The article compares Spanish with other foreign languages in the  Russian  school system, and considers its evolution in the  timeline  and the  impact on its status of migration movements in connection with political events, commercial and student exchange,  tourism;  as well as the  impact of certain measures taken both in Russia  and in Spain. Institutions in both countries have established links to promote mutual development in terms of learning Spanish and Russian,  and the  diplomatic corps has become the   catalyst and manager of  this  dynamic.  Despite the   fact  that the   reactions  of  educational  actors  (institutions, civil society, students  and  teachers) are  varied, they  reinforce different mechanisms to gain access  to Spanish culture and business, as well as to other Spanish-speaking countries. The article also demonstrates the  current statistics and describes the  trend that the  teaching of Spanish may  follow in the  coming years due to positioning of Spanish among the  main foreign languages studied in Russian  schools.